Analisis Perancangan Bilah Horizontal Axis Wind Turbin Jenis Taperless Dengan Airfoil NACA 4418 - Wahid Yusuf Ramadhan; Jojo Sumarjo; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
Wind speed in Indonesia only ranges from 3 meters/s to 11 meters/s, it is quite difficult to generate electricity on a large scale, it is also what makes the utilization of wind energy still very low. Wind turbine modifications need to be carried out by adjusting to low wind speed conditions to be able to produce optimal electrical energy. Therefore, a HAWT (Horizontal Axis Wind Turbine) blade design was made using NACA airfoils that have a high Cl / Cd value to produce 500 W of power at a wind speed of 1 meter / s – 12 meters / s. The study was conducted in 3 stages, First the calculation stage to determine the radius, chord and twist of the blade. The second stages is initial design of the blades were carried out by simulation using Q-Blade software to determine the NACA airfoil used and find out the coefficient performance and power produced. The last stages of blade design use solidworks software that produces a 3D blade design. The design results produced HAWT blades with Taperless type NACA 4418 airfoils with a blade radius of 0.9 m, chord width of 0.12 m, and a twist angle of 6.92° - 10.08°.